The Effectiveness of Termination of Prosecution in Settling Fraud Crimes Based on Restorative Justice - Janu Widono; Andri Winjaya Laksana (Jurnal Hukum Khaira Ummah, 2025)
This study aims to determine and analyze the implementation of the termination of prosecution in fraud crimes based on justice, the weaknesses of the termination of prosecution in fraud crimes based on restorative justice, and the effectiveness of the termination of prosecution in fraud crimes based on restorative justice. The approach method is sociological juridical, the research specification is analytical descriptive. The data used are primary and secondary data and the data collection method is field study and literature study, while the data analysis method uses qualitative analysis. The theories used are restorative justice theory, legal effectiveness theory and progressive legal theory. Based on the results of the study, it can be concluded that the implementation of the termination of prosecution in fraud crimes based on justice in the Pekalongan Regency District Prosecutor's Office has been carried out based on the Attorney General's Regulation Number 15 of 2020 concerning the Termination of Prosecution based on Restorative Justice and has reflected the theoretical principles of restorative justice. The weaknesses of the termination of prosecution in fraud crimes based on restorative justice have an impact on the termination of prosecution based on restorative justice not being able to run optimally and has not fully fulfilled the goals of recovery in the criminal justice system. The termination of prosecution in fraud crimes based on restorative justice has been effective, thus making the concept of recovery more acceptable than the retributive approach which emphasizes revenge.